2022
DOI: 10.7759/cureus.28031
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Nutritional Interventions on Key Cytokine Pathways in Rheumatoid Arthritis and Its Implications for Comorbid Depression: Is a More Comprehensive Approach Required?

Abstract: Rheumatoid arthritis (RA) is associated with both local and systemic inflammatory processes via the aberrant regulation of inflammatory pathways and imbalances in several mediators of inflammation. Cytokines, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1B, IL-6, IL-17, IL-18, rheumatoid factor, anti-cyclic citrullinated protein, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) have been used in diagnosing and tracking the progression of RA. The primary objective of this review is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The two eligible studies included in our meta-analysis also found no statistically significant differences in CRP, therefore, the outcome for ESR may be an odd random result. Regarding exercise, a previous meta-analysis showed that it decreased ESR [45], while several diet schemes are able to reduce ESR in RA patients [46]. Therefore, it is likely that our finding, i.e., the combined effect of diet and physical activity, which is based on a small number of studies, can be random.…”
Section: Completeness and Applicability Of Evidencementioning
confidence: 81%
“…The two eligible studies included in our meta-analysis also found no statistically significant differences in CRP, therefore, the outcome for ESR may be an odd random result. Regarding exercise, a previous meta-analysis showed that it decreased ESR [45], while several diet schemes are able to reduce ESR in RA patients [46]. Therefore, it is likely that our finding, i.e., the combined effect of diet and physical activity, which is based on a small number of studies, can be random.…”
Section: Completeness and Applicability Of Evidencementioning
confidence: 81%
“…However, gender affects this attachment style. Finally, diets such as an anti-inflammatory diet in rheumatoid arthritis and higher dietary inflammatory index food, macronutrients, and probiotics give a better outcome in regulating cytokine release, and disease progression correlated with depression [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions have been performed for the dietary pattern disease activity of rheumatoid arthritis [ 77 , 78 ].…”
Section: Natural Foods Phytochemicals and Chemical Compounds With Ant...mentioning
confidence: 99%